2010
DOI: 10.1590/s1413-78522010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo experimental da ação da metilprednisolona utilizada antes do traumatismo raquimedular em ratos Wistar

Abstract: Objective: To evaluate the effects of methylprednisolone used prior to spinal injury, both in relation to possible beneficial effects and to possible associated complications. Materials and methods: The study subjects were 32 Wister rats, divided into 4 groups. Two groups received drugs A (placebo) and B (methylprednisolone) immediately after the injury. Another 2 groups received the same drugs 4 hours before the injury. They were all evaluated over a period of 28 days to verify locomotor function and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
(25 reference statements)
0
5
1
2
Order By: Relevance
“…This finding suggests that methylprednisolone may attenuate the effects of the secondary lesion on the spinal cord, resulting in improvement of locomotor function at the cost of anti-inflammatory effects 18 , 24 26 . These findings conflict with those of Rabchevsky et al 27 and Marcon, 28 who did not observe functional improvements with the use of methylprednisolone.…”
Section: Discussioncontrasting
confidence: 75%
“…This finding suggests that methylprednisolone may attenuate the effects of the secondary lesion on the spinal cord, resulting in improvement of locomotor function at the cost of anti-inflammatory effects 18 , 24 26 . These findings conflict with those of Rabchevsky et al 27 and Marcon, 28 who did not observe functional improvements with the use of methylprednisolone.…”
Section: Discussioncontrasting
confidence: 75%
“…For example, genetic ablation of the alarmin IL-33 resulted in the long-lasting failure of monocyte infiltration following SCI but, surprisingly, an eventual decrease in neuronal survival and functional recovery compared with wild-type controls (127). Globally inhibiting inflammation using high doses of glucocorticoids has yielded conflicting results (72,108,155) and in some cases increased animal death following SCI (249). To be clear, the medical use of glucocorticoids such as methylprednisolone is no longer recommended in human cases of SCI due to significant complications (339).…”
Section: E Pleiotropic Effects Of Inflammationmentioning
confidence: 99%
“…To be clear, the medical use of glucocorticoids such as methylprednisolone is no longer recommended in human cases of SCI due to significant complications (339). The wound-healing properties of the late inflammatory response may be one explanation of how complete ablation of inflammation following SCI worsens functional outcome (104,127,249).…”
Section: E Pleiotropic Effects Of Inflammationmentioning
confidence: 99%
“…Gangliosides, a glycolipid molecule derived from sialic acid, in vitro studies have observed that gangliosides, help in increasing the formation and growth of neurites, protoplasmic expansions of axons that originate new functional connections, induce neuronal regeneration, and promote neuroplasticity [106]. In case of SCI most studied ganglioside is GM1, studies have observed that SCI subjects who are receiving GM1, ganglioside has much more improvement in sensory and motor functions along with sphincter function in comparison to subjects who are on placebos [107]. In incomplete SCI subjects who received GM1in combination with physical therapy have improved motor scores and walking velocity and distance in comparison to subjects who were either on placebo or physical therapy alone [108].…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…In traumatic SCI subjects with neurological damage, have recommended ganglioside loading dose is 300 mg for 30 days, i.e., 100 mg once daily via intravenous or intramuscular injection. Ganglioside should not be administered simultaneously with methylprednisolone [107].…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%